Rhetoric matters: A social norms explanation for the anomaly of framing - Chang, Daphne; Chen, Roy; Krupka, Erin (Games and economic behavior, 2019)
Ample evidence shows that certain words or ways of phrasing things can cause us to change our preferences. We demonstrate one mechanism for why this happens - “framing” evokes norms which then influence choice. We use a laboratory study to test the impact of describing a series of dictator games with either politically charged tax- or neutrally-framed language. Subjects' political identities interact with these frames, causing changes in both norms and choices. Framing makes Democrats prefer equalized outcomes, and Republicans reluctant to redistribute payments even when it leaves them disadvantaged.